Desenvolvimento profissional e implementação de material curricular: contribuições e desafios a serem enfrentados a partir da metodologia estudo de aula - Merichelli, Marco Aurélio Jarreta (2018)
This work investigates the professional development of teachers who teach mathematics in the 3rd year of elementary school and discusses the implementation of the EMAI curriculum material in schools of the public state of São Paulo located in the eastern zone of the capital from a teacher training that was used of a methodology of training of teachers called Classroom Study (CURI, 2016). This training was offered in 2015 through a partnership between Cruzeiro do Sul University and the Regional Office of Eastern Teaching I. Over a year, teachers and trainers met biweekly at the university's premises to plan and reschedule classes which were being carried out in schools and were filmed so that teachers could attend each other's classes. Among the classes studied, four episodes (corresponding to the four axes of the mathematics curriculum for basic education) were selected, and the data were analyzed from the categories defined by Brown (2009) for curricular implementation processes, based on the definitions of professional development pointed out by Marcelo (2009) and in the knowledge of the teacher who teaches mathematics mapped by Ball, Thames and Phelps (2008). It was hypothesized that the use of the Classroom Methodology in teacher training could bring significant contributions both to professional development and to curricular implementation, and it was observed the confirmation of this insofar as the professional development could be observed as it is characterized and that the curricular implementation took place in the manner recommended by the literature.